ASPEK PSIKOLOGIS DAN METODOLOGIS DALAM PENGAJARAN BAHASA ARAB DI IAIN SURAKARTA - Ahmad Fauzi (Millah: Journal of Religious Studies, 2016)
Students are learners with all the attributes attached to them. It is, therefore, necessary for monitoring and evaluating the educational institutions mainly to monitor students progress. For this reason, this study aims at explaining the problems and solutions in the Arabic language teaching IAIN Surakarta. The review of the research is to identify, describe, and analyze a variety of Arabic language teaching methods in conjunction with the psychological aspects of the students.This study used a qualitative approach. The reason for using the approaches and techniques of the research is that the main activity of the research is describing the instructional activities, considered problem concerning instructional activities which require description. Technique of data collection are interview, observation and documentation. For checking the validity of the data is done by Trianggulasi. The analysis of the data is interactive analysis which is done stimultaneously: data reduction, presentation and conclusion/verification.The result showed some fact which are supportered by the manjority of subjects, that the demonstration method in teaching Arabic is facilitating students in understanding the material it stimulated the internal positive mental process of the students. Demonstration method itself is a method of teaching through a specific model which makes teacher have a special ability to stimulate the class Besides, the students themselves personally that play a role in build a positive mental